The Relationship between Attachment Styles and Resiliency with Attitudes to Drug Use in Students - Jafar Bahadori; Toraj Hashemi; Mansour Bayrami (Drug Control Headquarters, Research and Education Office, 2010)
Objective: Drug use and addiction as a major trauma mental- social century, various groups, especially youth and students will always be threatened. The aim of present study was to investigate the relationship between attachment styles and resiliency with attitude to drug use in boy students Tabriz University. Method: This study was descriptive-correlation. The statistical populations consisted of all boy students Tabriz University academic year of study 1389-90, which of these, 200 boys were selected cluster sampling. To collect data was used from Hazan & Shaver Adult Attachment Scale of, Connor-Davidson Resiliency Questionnaire, Vide Attitudes to Drug use Scale. The data were analyzed by using of Pearson correlation and multiple regressions by SPSS. Results: Finding revealed that attitude to drug addiction has negative relationship with secure attachment styles and positive relationship ambivalent and avoidant insecure attachment styles. On the other hand, attitude to drug addiction have negative relationship with resiliency. Also result of regression analysis showed that the attachment styles and resiliency can predict changes in drug addiction attitude. Conclusion: Based on finding with growth secure attachment styles family with children and also use resiliency program can reduce attitudes to drug use in students.